Unmasking the Stranger American Welfare Residency Rules and the Encounter with the Other - M. Fallinger (Law Text Culture, 2000)
One American welfare doctrine that refuses to die embarrasses the American optimist-modernist credo that time always brings progress. That doctrine, most recently resurrected in President Clinton's welfare reform legislation, the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 (PRWORA), permits states to impose what euphemistic bureaucrats call a "durational residency requirement" on impoverished citizens seeking government assistance to provide food, clothing, and shelter for their families. Where this rule once meant that impoverished citizens could be denied all welfare benefits for up to a year after they moved to a new state, in its current less draconian form, the PWRORA residency rule permits an individual state to provide the lesser of either its own minimum benefit or the benefit from the newcomer's state of origin for a year. However, this apparently kinder and gentler doctrine has ominous consequences for real people: for example, Edwin and Maria Delores Maldonado, who moved from Puerto Rico received 304 per month (the benefit level in Puerto Rico) when they arrived at their new home in Pennsylvania, instead of the 836 per month that Pennsylvania's long-term needy residents were getting to meet their subsistence needs. Similarly in Roe v. Anderson, a case argued in the United States Supreme Court in early 1999, the lower federal court noted that a family of four moving from Mississippi, where 144 would provide a subsistence living, would be hard-pressed to survive on that amount in Los Angeles, where the highest housing costs help push the minimum subsistence level for that family to 673 a month.